Does Temporal Expectation Driven by Rhythmic Cues Differ From That Driven by Symbolic Cues Across the Millisecond and Second Range?. (June 2019) - Ren, Yanna; Xu, Zhihan; Wu, Fengxia; Ejima, Yoshimichi; Yang, Jiajia; Takahashi, Satoshi; Wu, Qiong; Wu, Jinglong
Temporal expectation relies on different predictive information, such as regular rhythms and symbolic cues, to direct attention to a future moment in time to optimize behaviour. However, whether differences exist between temporal expectations driven by regular rhythms and symbolic cues has not been clearly established. In this study, 20 participants performed two temporal expectation tasks in which a rhythmic cue or a symbolic cue indicated (70% expected) that the target would appear after an interval of 500 ms (short), 1, 500 ms (medium), or 2, 500 ms (long). We found larger cueing effects for the rhythmic cued task than for the symbolic cued task during the short interval, indicating that rhythmic cues were more effective in improving performance. Furthermore, no significant difference was found during the longer interval, reflect that the behavioural differences between the two forms of temporal expectations were likely to diminish as the time interval increased. Thus, we speculate that the temporal expectation driven by rhythmic cues differs from that driven by symbolic cues only in the limited time range; however, the mechanisms underlying the two forms of temporal expectations trend to become more similar over increasing temporal scales.